Enhancing Arabic Writing and Literacy through Ibda’ Magazine: A Culturally Relevant Medium in Islamic Boarding Schools - Lazuardi, Achmad Makki; Hanifansyah, Nur; Mahmudah, Menik; Wahyudi, Iqmal (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2025)
In Arabic language education, writing remains one of the most underdeveloped yet essential skills, particularly for non-native learners who often excel in grammar drills but struggle to produce coherent and expressive texts. This study explores the role of Ibda’ Magazine as an authentic, student-centered platform to enhance Arabic writing skills and literacy among 60 third-year Tsanawiyah students at Pondok Pesantren Darullughah Wadda’wah. Using a qualitative descriptive design, the research draws on thematic analysis of student writings, classroom observations, and semi-structured interviews with both learners and instructors. The findings reveal significant improvement in students' vocabulary use, grammatical accuracy, narrative coherence, and stylistic expression. Additionally, learners reported increased confidence, motivation, and a deeper sense of ownership over their Arabic writing. The study affirms that culturally relevant, print-based media can serve as powerful pedagogical tools in bridging the gap between formal instruction and meaningful language practice, offering new pathways for Arabic writing development in Islamic educational settings.